High spice prices in Comoros - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The 2000 market prices for vanilla and cloves have reached their highest level for ten years in the Comoros, thanks to the cyclone which devastated vanilla plantations in neighbouring Madagascar (the world s largest producer) and the unrest in...